Judicial activism and legislative omissions: the effects of the “procreative tourism” on the Italian legal order (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The essay analyzes the different role played both by the Courts and the Parliament in addressing the issue of the legal effects of the “procreative tourism” on the Italian legal system.
Keywords: Medically Assisted Reproduction; procreative tourism; counterlimits; separation of powers; best interests of the child